Original paper Cardio-renal anemia syndrome in hemodialyzed patients - Małyszko, Jacek; Małyszko, Jolanta; Myśliwiec, Michał (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2009)
Introduction: Recently the anemia was found to be one of the arms of the cardio-renal anemia syndrome (CRA) in chronic kidney disease patients not on dialysis. The correction of anemia was effective in the amelioration of both cardiac and renal failure. Aim: To study the prevalence CRA syndrome in chronic hemodialyzed patients. Material and methods: One hyndred patients on hemodialyses (at least 3 month, age 18 or higher). Definition of the severity of the CRA in dialysis patients: NYHA class (1-4 points), degree of anemia (1-4 points), presence of diabetes (0-1 point), age (more and less than 65 years) (0-1 point), gender (0-1 point). In the population studied females accounted for 48% of patients, 34% were diabetic, 64% were over 65 years of age, only 27% had hemoglobin level higher than 11 g/dl, 36% had chronic heart failure according to NYHA class. Results: In this population prevalence of pamaters of CRA syndrom is relatively high, thus in older patients (i.e. over 65 years) is accoiated with high cardiovascular mortality (the most common cause of death in hemodialyzed subjects).